The Board of Rites and the making of Qing China - Keliher, Macabe (University of California Press, 2020)
"In 1631, Manchu state-makers set up an administrative apparatus that included a ministry for implementing and legislating rites and rituals, the Board of Li, or the Board of Rites. Over the next sixty years the Board of Li helped develop the rules and regulations of the Manchu state, which were codified in an administrative code in 1690. This book looks at the role of li (ritual) and the Board of Li in early Manchu state-making efforts. More than simply rituals and ceremonies, as often assumed, li was intimately tied to the formation of politics and administration. Macabe Keliher argues that culture and society are mutually formed, each constructed simultaneously by actors in order to organize themselves politically and to orient themselves ontologically, resulting in the emergence of different administrative and institutional forms, not only in Chinese history but also across the Eurasian continent. This new major approach to the formation of the Qing empire moves beyond traditional understandings of war and bureaucracy and state-making to reshape our understanding of this period of Chinese history"--Provided by publisher.